re-operative Teaching is Important on Post-operative Self-care Activities among Cardiac Surgery Patients: An Overview - Singh Baghel, Arvind; Solomon, Smriti G. (Innovational: Journal of Nursing and Healthcare, 2024)
The patient will experience stress before undergoing any form of surgery. The fact that the heart is such an essential organ results in an increase in the amount of stress experienced. Some patients may experience feelings of helplessness, insecurity, and isolation as a response to the inconvenience, distress, and anxiety brought on by their stitches breaking. The all-encompassing pre-operative education can contribute to a reduction in the intensity of these feelings. Pre-operative education is an important component of the approaches for improved recovery after surgery, which aims to empower patients and their families to make their own health decisions. Pre-operative education reduces hospital stays, surgical complications, and recovery time. Thorough pre-operative instruction helps patients cope with surgery, control pain, and self-care. Post-operative problems, compliance, and anxiety must be reduced. According to a study on self-care knowledge and performance, early extubating, pain management, duration of stay, and complications, scheduled pre-operative training may help patients. Pre-operative teaching can prepare cardiac surgery patients. According to a study on the effect of the Orem self-care program on sleep quality, daily activities, and lower extremity edema in patients undergoing coronary artery bypass graft surgery, the program can reduce post-operative complications and improve self-care in long-term care patients.